Dental care of hospitalized pediatric patient with tetralogy of Fallot: a case report - CHANDLER,Claudia Lobelli (2022)
ABSTRACT Tetralogy of Fallot is the most prevalent cyanotic congenital heart disease and it has a high mortality rate. The aim of this article was to provide a clinical case, describing the dental treatment of an infant patient with tetralogy of Fallot done at a hospital. The patient was a 7-year-old male, lived in a rural area with no previous diagnosis of this cardiopathy when he was attended to by a multidisciplinary team at University Hospital Ana Bezerra, at Santa Cruz, Northern Rio Grande, Brazil. After his medical appointment, the patient received a visit from the dental resident in Mother-Infant Health in his hospital room. During the dental exam, multiple carious lesions were found and there was an urgent need to reduce the risk of dental infection before the patient underwent heart surgery. The treatment started with a preventive approach, including oral hygiene instruction and behavior management. The treatment was completed using the atraumatic restorative technique, and a root tip was extracted. Antibiotic prophylaxis was administered before the extraction to minimize the risk of infectious endocarditis. After the dental treatment, the multidisciplinary team referred the patient for surgery to address the tetralogy of Fallot. The integration between the multidisciplinary residency and the medical team was important to reduce the risks of infectious endocarditis during the dental treatment, aiming to provide integral care to this patient.